Profil Penggunaan Antikoagulan pada Pasien COVID-19 dengan Komorbid Hipertensi di Rawat Inap RSUD Panembahan, Bantul, Yogyakarta - Rahmat A Hi Wahid; Anis Febri Nilansari; Fitri Andriani Fatimah (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2023)
Hypertension is the highest comorbid group in COVID-19 patients, followed by diabetes mellitus and heart disease. The increase in coagulopathy and thromboembolism secondary to COVID-19 has received global attention, with several surveys and reports of increased mortality. The use of anticoagulants in the treatment of COVID-19 patients needs to be done. This study aims to determine the profile of the use of anticoagulants in COVID-19 patients with hypertension who are hospitalized in Panembahan Hospital, Senopati, Bantul, Yogyakarta. The research method is descriptive observational research using secondary data in the form of medical records. Data were taken retrospectively from the medical records of COVID-19 patients with hypertension who were hospitalized at Panembahan Hospital, Bantul, Yogyakarta for the period 2020-2021. A total of 67 medical records met the inclusion criteria, 46 patients (68.7%) were given anticoagulants and 21 patients (31.3%) were not given anticoagulants. The highest use of anticoagulants was in the age group of 55-65 years (n=28) and 30-54 years (n=21). Heparin (11.9%) and Rivaroxaban (9%) were the single anticoagulants most frequently used for hospitalized COVID-19 patients at Panembahan Hospital, Bantul, Yogyakarta. While the most used combinations were Heparin with Rivaroxaban (20.9%), and Enoxaparin with Rivaroxaban (9%).